Nursing Staff Representation in Brazilian Heath Management: An Integrative Literature Review - , Kélia das Graças de Paiva Macias Nakai; , Yandra Mariana da Conceição Campos; , Andressa Torres Oliveira; , Márcia do Socorro Correia Correia; , Shirley Helena dos Santos Henriques da Silva; , Leonardo Silva da Costa; , Annely Barros Góis; , Regina Correia Lanzana Araujo da Silva; , José Ismar dos Santos Sousa; , Antônio Carlos Silva Azevedo; , Lis Ferreira Barbosa; , Sandy Costa dos Santos; et al. (Archives of Current Research International, 2025)
Background: In recent decades, nursing has increasingly assumed strategic roles in hospital management, contributing not only to care delivery but also to the planning, organization, and evaluation of health services. The complexity of contemporary healthcare demands that nurse managers develop managerial competencies that go beyond clinical expertise, encompassing leadership, decision-making, and team coordination. However, the recognition of nursing as a key player in hospital governance remains a challenge in many contexts, especially in Brazil, where structural, educational, and cultural barriers may limit the full exercise of this role. Objective: To analyze the representativeness of nursing staff in Brazilian health management, identifying the required competencies, the challenges faced and the impacts of this role on the quality of care. Methods: This is an integrative review, with a qualitative approach, carried out in the SciELO, LILACS, BDENF and PubMed databases, with a selection of articles published between 2018 and 2024, in Portuguese, English or Spanish. The descriptors used were “nursing”, “hospital management” and “health leadership”. Results: The results were organized into three thematic categories: (1) the managerial competencies necessary for the role of the nurse manager, such as leadership, strategic planning, decision-making and effective communication; (2) the challenges faced in the exercise of management, highlighting work overload, scarcity of resources, team resistance and the lack of specific training in management; and (3) the positive impacts of the presence of nurses in hospital leadership, such as improvements in the quality of care, reduction of adverse events, increased patient satisfaction and appreciation of humanization in care. Conclusion: It is concluded that nursing has expanded its presence in hospital management, but still needs greater institutional recognition, investment in management training and organizational support. The appreciation of the role of nurse managers is strategic to promote more humane, problem-solving and integrated management models in care practices.